Expansion of chronic MS lesions is associated with an increase of radial diffusivity in periplaque white matter - Klistorner, Samuel; Barnett, Michael H; Yiannikas, Con; Barton, Joshua; Parratt, John; You, Yuyi; Graham, Stuart L; Klistorner, Alexander (Multiple sclerosis, 2022)
Expansion of chronic multiple sclerosis (MS) lesion is associated with slow-burning inflammation at lesion rim. However, the underlying mechanisms leading to expansion are not fully understood. To investigate the relationship between diffusivity markers of demyelination and axonal loss in perilesional white matter and lesion expansion in relapsing-remitting MS (RRMS). T1, FLAIR and diffusion tensor images were acquired from 30 patients. Novel single-streamline technique was used to estimate diffusivity in lesions, perilesional white matter and normal-appearing white matter (NAWM). Significant association was found between baseline periplaque radial diffusivity (RD) and subsequent lesion expansion. Conversely, periplaque axial diffusivity (AD) did not correlate with lesion growth. Baseline RD (but not AD) in periplaque white matter of expanding lesions was significantly higher compared with non-expanding lesions. Correlation between increase of both RD and AD in the periplaque area during follow-up period and lesion expansion was noticeably stronger for RD. Increase of RD in periplaque area was also much higher compared to AD. There was significant increase of AD and RD in the periplaque area of expanding, but not in non-expanding, lesions. Periplaque demyelination is likely to be an initial step in a process of lesion expansion and, as such, potentially represents a suitable target for remyelinating therapies.